Health behaviors and problems in Polish homeless men - Bernadetta Repka; Bernadetta Repka; Grzegorz Bejda; Agnieszka Kułak-Bejda; Damian Czarnecki; Marcin Ziółkowski; Anna Mosiołek; Agata Szulc; Napoleon Waszkiewicz; Anna Ślifirczyk; Wojciech Kułak; Elżbieta Krajewska-Kułak (Frontiers Media S.A., 2023)
IntroductionHomelessness is considered to be a global problem, independent of the material situation of a given country and occurring in most societies around the world.Aim of the studyAssessment of the preferred health behaviors of homeless people.Materials and methodsThe study covered 153 men who are homeless and 312 men who are not homeless. The original questionnaire of homeless, and validated the Satisfaction with Life Scale (SWLS), the Health Behavior Inventory (HBI), the General Self-Efficacy Scale (GSES) and the Multidimensional Health Locus of Control (MHLC) Scale were used. The research covered fully completed questionnaires from 153 homeless men staying in Białystok and Gdańsk homelss centers.ResultsOn average, the homeless men assessed their health at 6.0 ± 2.7 points, and the non-homeless at 7.8 ± 2.2 points (p < 0.001). Significant differences were found between people experiencing a homelessness crisis and the control group in selected aspects concerning the everyday life hygiene of the respondents, health self-assessment, declarations of visits to a specialist and carrying out check-ups, level of satisfaction with life, coping with difficult situations, preferred pro-health behaviors and dimensions of health control. In the used scales, SWLS, HBI, GES, and MHCL, the majority of homeless men obtained average scores. They were rather dissatisfied with their lives, with a low level of effectiveness in coping with difficult situations and obstacles, a low level of health behaviors, and in the scope of health, control increasing the impact of chance.ConclusionThe level of the presented health behaviors showed statistically significant diversification with all dimensions of the health locus of control, and its internal dimension with age, homelessness phase, the respondents' criminal history, being under constant medical care, and self-assessment of health.